2020
DOI: 10.1126/sciadv.aaz4344
|View full text |Cite
|
Sign up to set email alerts
|

MAP6 is an intraluminal protein that induces neuronal microtubules to coil

Abstract: Neuronal activities depend heavily on microtubules, which shape neuronal processes and transport myriad molecules within them. Although constantly remodeled through growth and shrinkage events, neuronal microtubules must be sufficiently stable to maintain nervous system wiring. This stability is somehow maintained by various microtubule-associated proteins (MAPs), but little is known about how these proteins work. Here, we show that MAP6, previously known to confer cold stability to microtubules, promotes grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(80 citation statements)
references
References 51 publications
2
77
1
Order By: Relevance
“…It may be that constraining the protein within the microtubule lumen induces secondary structure formation. However, when microtubules were co-polymerized with MAP6 in vitro, the globular intraluminal particles which form (Cuveillier et al, 2020) did not exactly resemble the densities we observed in DRG axons. Another possibility is that MAP6 brings together intraluminal proteins such as actin (Paul et al, 2020) or α-TAT (Coombes et al, 2016;Szyk et al, 2014) to form an ordered, ring-like structure.…”
Section: Drg But Not Dm Microtubules Have Consistent 13 Pfcontrasting
confidence: 74%
See 1 more Smart Citation
“…It may be that constraining the protein within the microtubule lumen induces secondary structure formation. However, when microtubules were co-polymerized with MAP6 in vitro, the globular intraluminal particles which form (Cuveillier et al, 2020) did not exactly resemble the densities we observed in DRG axons. Another possibility is that MAP6 brings together intraluminal proteins such as actin (Paul et al, 2020) or α-TAT (Coombes et al, 2016;Szyk et al, 2014) to form an ordered, ring-like structure.…”
Section: Drg But Not Dm Microtubules Have Consistent 13 Pfcontrasting
confidence: 74%
“…Although globular MIPs were initially observed over 50 years ago (Echandia et al, 1968), their constituents remain unclear. Recent work proposed they contain microtubule associated protein 6 (MAP6, previously called N-STOP) (Cuveillier et al, 2020), which is known to promote formation of cold-stable microtubules in neurons (Guillaud et al, 1998). Analysis of mouse MAP6 showed it is highly disordered and lacks secondary structure apart from two short helices (Figure S3B).…”
Section: Drg But Not Dm Microtubules Have Consistent 13 Pfmentioning
confidence: 99%
“…There is wealth of information for many other contemporary lines of investigation, such as detailed descriptions of MT behaviors during axon branching ( Yu et al, 1994 ), of the ultrastructure of growth cones, dendrites, and synapses ( Peters et al, 1991 ), or of curious phenomena such as impressive packages of ER-derived tubular structures found in certain axons ( Andres, 1965b ; Peters et al, 1991 ). Axonal MTs of species as diverse as cockroach, lamprey, frog, toad, chick, mouse, and rats were reported to contain luminal material in form of a ∼4-nm-thick central dot or filament ( Andres, 1965a ; Burton, 1984 , 1987 ; Gonatas and Robbins, 1965 ; Lane and Treherne, 1970 ; Nixon et al, 1994 ; Rodríguez Echandía et al, 1968 ; Smith et al, 1970 , 1975 ; Wuerker and Palay, 1969 ), matching recent reports of MTs with incorporated actin filaments or MAP6/stable tubule-only peptide ( Cuveillier et al, 2020 ; Paul et al, 2019 Preprint ), of which the latter could help to explain long-term cold resistance of axonal MTs observed in vivo ( Delphin et al, 2012 ; Pannese et al, 1982 ; but see also Song et al, 2013 ). Furthermore, classical studies revealed the presence of post-translationally modified subdomains in MT lattices ( Baas and Ahmad, 1992 ; Baas and Black, 1990 ; Baas and Joshi, 1992 ), which start finding their explanations in current models of MT stability ( Baas et al, 2016 ).…”
Section: Introductionsupporting
confidence: 67%
“…Additionally, structural MAPs can regulate the number of MT protofilaments [102]. Interestingly, it seems that MAP6 has unique properties and functions as it is a microtubule luminal protein and protects MTs against drug and cold-dependent destabilization [113]. With the exception of MAP4, which is a ubiquitous protein, and the expression of MAP7 in epithelial cells, the expression of structural MAPs is mainly restricted to the brain [114].…”
Section: Microtubule-associated Proteins and Microtubule Dynamicsmentioning
confidence: 99%